THE ROLE OF BUSINESS TRUST, CONSUMER CONFIDENCE AND THE DEVELOPMENT OF INFORMATION AND COMMUNICATION TECHNOLOGY ON ECONOMIC GROWTH IN G20 COUNTRIES - Hardiansa Nur Syahputra; Marselina Marselina; Neli Aida (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2021)
This study aims to analyze the condition of business trust, consumer trust, rule of law, developments in technology,information, and communication, and their influence on ASEAN economic growth. The data used is panel dataconsisting of time series data for 2009 – 2020 and a cross-section of 10 countries with the highest level of businessconfidence in G20 Member countries. The variables used are economic growth, conditions of business trust,consumer confidence, rule of law, development of technology, information, and communication. The analyticaltool used is panel data regression, namely the Fixed Effect Model (FEM). An increase in business confidence andconsumer confidence will have an impact on increasing economic growth. In the research results, business trust has the most influence. Keywords: Economic Growth, Conditions of Business Trust, and Consumer Confidence. Abstrak Penelitian ini bertujuan untuk menganalisis kondisi kepercayaan bisnis, kepercayaan konsumen, supremasi hukum, perkembangan teknologi, informasi, dan komunikasi, serta pengaruhnya terhadap pertumbuhan ekonomi ASEAN. Data yang digunakan adalah data panel yang terdiri dari data time series tahun 2009 – 2020 dan cross section dari 10 negara dengan tingkat kepercayaan bisnis tertinggi di negara-negara Anggota G20. Variabel yang digunakan adalah pertumbuhan ekonomi, kondisi kepercayaan bisnis, kepercayaan konsumen, supremasi hukum, perkembangan teknologi, informasi, dan komunikasi. Alat analisis yang digunakan adalah regresi data panel yaitu Fixed Effect Model (FEM). Meningkatnya kepercayaan bisnis dan kepercayaan konsumen akan berdampak pada peningkatan pertumbuhan ekonomi. Dalam hasil penelitian, kepercayaan bisnis memiliki pengaruh paling besar. Kata Kunci: Pertumbuhan Ekonomi, Kepercayaan Bisnis, dan Kepercayaan Konsumen.